SEJARAH PEMBENTUKAN KABUPATEN KEPULAUAN ANAMBAS PROVINSI KEPULAUAN RIAU (2008-2014) - Fithri Diniati S Fithri Diniati S; Isjoni Isjoni '; Kamaruddin Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Indonesian region is a dynamic region which has developed from time backwards, towards progress. Regional expansion is just one example is one example of the changes taking place in Indonesia. Expansion of a district is a reflection of regional autonomy, through the expansion process occurs because the powers of administrative autonomy in Indonesia. In this reform era, the development of the area will increase the overall national development. This is the concept of regional autonomy in Indonesia runs. As the main hope of autonomy territory is achieving the tasks of government well. Through regional expansion, the relationship between government officials and the public is getting closer, and the government apparatus it self increasingly have the ability to carry out the development of the nation and provide services to the community. This is because the relationship between government and society is getting shorter, as well as development planning is getting smaller. Along with the authority of local autonomy, Natuna then regional expansion districts, which by the end of 2008 to 19 districts with the addition, District Palmatak, Subi, Bunguran North Sea island, Pulau Tiga, Bunguran Northeast, Bunguran Central, Bunguran South, Serasan South, East Siantan, South Siantan, Jemaja East and Central Siantan. Along with the expansion of district that aims to shorten the control range, appears aspiration to make the Group of Anambas as its own autonomous region. Through a long struggle both at central and regional levels, Anambas Island finally formed through Law No. 33 Year 2008 dated June 24, 2008. Anambas Island consists of 7 District of the District Siantan, District East Siantan, District of South Siantan, District Central Siantan, District Palmatak. Jemaja sub-district and District East Jemaja.Keywords: History, Formation, Anambas Island